Development and Testing of Identity Fusion Instruments - Asrila, Agitia Kurniati; Akmalia, Navissa; Deri, Putri Sukma (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
The existence of complex dynamics in the behavior of individuals in groups can explain the theoretical constructs of individual and group relations that continue to develop today. One of the developed theoretical contracts is the theory of identity fusion. This study aims to compile an identity fusion scale based on Gomez, Swann, Vazquez, Brooks, Buhrmester, & Jetten's verbal identity fusion scale in 2011. There are several processes for compiling a measuring instrument in this study. First, by conducting an open-ended questionnaire to find behavioral indicators that emerged. The second is to test the content validity using Aiken's V content validity coefficient value. Third, to test the construct validity by doing Confirmatory Factor Analysis (CFA). Fourth is to test the validity of the criteria by correlating the scale of identity fusion and social identity. Finally, the researcher estimated the reliability of the final item compilation. The results showed that 27 items could use to measure verbal identity fusion, with a Cronbach alpha coefficient of 0.935. Based on the correlation results, there is a positive relationship between identity fusion and social identity. Although there are different perspectives in explaining individual behavior, the fusion of identity and social identity is a complementary and related construct.